2015
DOI: 10.1177/0003489415617776
|View full text |Cite
|
Sign up to set email alerts
|

Oxymetazoline Applied Topically to the Nasal Mucosa Decreases Trans-Mucosal Nitrous Oxide Exchange for the Middle Ear

Abstract: Objective: Determine if the middle ear (ME) trans-mucosal nitrous oxide (N2O) gas exchange rate can be pharmacologically modulated by the nasal application of a vasoconstrictor. Methods: In a randomized, double-blind, crossover study, 20 adults received a nasal spray challenge containing either oxymetazoline or saline (placebo). At each session, subjects were fitted with a non-rebreathing mask and breathed room air for 20 minutes, 50% N2O:50% O2 for 20 minutes, and 100% O2 for 10 minutes. Throughout, heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
6

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 25 publications
1
9
1
6
Order By: Relevance
“…Simulations 5 and 6 predict that a downgraded ET opening efficiency will be expressed as a less efficient MEPR for those periods which is accompanied by a consequent negative shift in the EV-MEEPG, effects validated by the change in MEEPG (tympanometric pressure) observed for children and adults during natural and experimental upper respiratory viral infections (Antonio et al, 2002; Buchman et al, 1995; Moody et al, 1998). In addition, emergent features of the model such as physiologic ME species-pressures (Simulation 6), the negative EV-MEEPG for all ET opening efficiencies not equal to 1 (Simulation 3), and the perfusion-limitation on the rate of MEEPG change (Simulations 2, 3) are consistent with clinical measurement (Antonio et al, 2002; Felding et al, 1987; Hergils et al, 1990; Hergils et al, 1997; Moody et al, 1998; Sade et al, 1993) and experimental results (Buchman et al, 1995; Teixeira et al, 2015; Teixeira et al, 2016). …”
Section: 0 Discussionsupporting
confidence: 65%
“…Simulations 5 and 6 predict that a downgraded ET opening efficiency will be expressed as a less efficient MEPR for those periods which is accompanied by a consequent negative shift in the EV-MEEPG, effects validated by the change in MEEPG (tympanometric pressure) observed for children and adults during natural and experimental upper respiratory viral infections (Antonio et al, 2002; Buchman et al, 1995; Moody et al, 1998). In addition, emergent features of the model such as physiologic ME species-pressures (Simulation 6), the negative EV-MEEPG for all ET opening efficiencies not equal to 1 (Simulation 3), and the perfusion-limitation on the rate of MEEPG change (Simulations 2, 3) are consistent with clinical measurement (Antonio et al, 2002; Felding et al, 1987; Hergils et al, 1990; Hergils et al, 1997; Moody et al, 1998; Sade et al, 1993) and experimental results (Buchman et al, 1995; Teixeira et al, 2015; Teixeira et al, 2016). …”
Section: 0 Discussionsupporting
confidence: 65%
“…Because the post-challenge ME pressure trajectory is the main outcome variable for the present study, we considered the possibility that the pattern of ME pressure increase observed here signaled a change in MEM volume and not an increased MEM blood perfusion rate. However, we discounted that data interpretation because, 1) MEM swelling occurs quickly which would cause a rapid ME pressure response that is not consistent with the slow, progressive increase that characterized our data, 2) mathematical simulations of the experiment show that any reasonable change in MEM volume would have a very small effect on ME pressure, and 3) past experiments that used a similar design format and vasoactive agents to drive the response reported changes in the ME pressure trajectory similar to that observed in the present study 12,13 .…”
Section: Discussioncontrasting
confidence: 50%
“…The unified airway response predicts that regional application of a noxious, inflammatory stimulus will provoke both local and distal mucosal inflammation. Here, topical application of histamine to the nasal mucosa was used as the regional stimulus 16,18 and the trans-MEM N 2 O exchange-rate, a direct measure of the MEM blood perfusion rate 10 , was measured as the distal inflammatory response 12,13 . The confounding effect of ET openings on that response measure were reduced by reclining the subjects to decrease ET opening efficiency and instructing them to limit “swallowing” during the period of data collection, and eliminated by restricting the data analysis to time periods with no evidence of active or passive ET openings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations